Treatment of Major Depressive Disorder with Autism Spectrum Disorder by Acceptance and Commitment Therapy Matrix - Takafumi Watanabe (Case Reports in Psychiatry)
Autism spectrum disorder (ASD) is known to increase a variety of psychiatric disorders, including major depressive disorder (MDD). Acceptance and commitment therapy (ACT) has been reported to be an effective psychotherapy for MDD. However, this is not the case with ASD. In this case study, based on the hypothesis that it is effective in treating MDD with ASD, we adapted the ACT Matrix, a tool for visualizing an individual’s experiences in the context of ACT, and administered 15 sessions to a woman with MDD with ASD following the onset of photo dermatosis. By the end of the final session, there was an increase in value-based behaviors and significant changes in depressive symptoms as well as significant changes in process measures such as experience avoidance, mindfulness, and progress toward a valued life. Six months after the end of the session, the improvement in symptoms was even stronger and the process measure of obstruction to a valued life was significantly improved. The ACT Matrix may thus ameliorate MDD in patients with ASD.